Environmental protection tax and total factor productivity—Evidence from Chinese listed companies - Sun, Xiaoke; Zhang, Cuiyan (Frontiers in Environmental Science, 2023)
By improving its total factor productivity, China may attain higher quality and more sustainable economic growth. As a key market-based incentive for environmental regulation, does environmental protection tax increase total factor productivity and provide a win-win situation for both economic and environmental performance? It is a debate-worthy topic. Based on data of Chinese listed companies, this paper uses the triple difference method to analyze China's environmental protection tax reform as a natural experiment. The results show that the environmental protection tax can significantly boost the firm's total factor productivity by encouraging technological innovation and enhancing resource allocation. Based on analysis of heterogeneity, it appears that state-owned enterprises, larger corporations, and regions with more strict environmental enforcement are more responsive to environmental protection tax policies. This report provides critical empirical evidence for upgrading China's tax framework to protect the environment.